Pengaruh Penggunaan Kartu Debit dan Uang Elektronik (E-Money) Terhadap Pengeluaran Konsumsi Mahasiswa - Laila Ramadani (Jurnal Ekonomi dan Studi Pembangunan, 2016)
This study aims to determine the effect of the use of debit cards and electronic money to consumption expenditure Development Economics of students, State University of Malang. The type of this research is quantitative research, and data used is primary data from questionnaires. The analysis technique used is multiple linear regression analysis. Sample in this research is 150 students out from 240 students in Development Economics, Faculty of Economics, State University of Malang. The results indicate that according to the hypothesis test there is a positive and significant influence between the use of debit cards and electronic money to consumption expenditure of Development Economics student, State University of Malang students of 2014. The use of debit cards and electronic money also affect the students consumption expenditure. It is caused by non-cash payments are easy to use. Psychologically, anyone will spend their money easier in non-cash payment than in cash form. The results of this research indicate that Development Economics students in State University of Malang are consumptive. Keywords: e-money, consumption expenditure, debt card